Hydrogen production from aluminum-water reactions subject to varied pressures and temperatures - Godart, Peter; Fischman, Jason; Seto, Kelsey; Hart, Douglas (International journal of hydrogen energy, 2019)
The production of hydrogen via an aluminum-water reaction is explored at temperatures and pressures ranging from 273.15 to 600 K and 0.1–10 MPa, respectively. Across this range, aluminum and water can react to form different aluminum oxide and hydroxide species, resulting in differences in the release of thermal energy, as well as the amount of water required stoichiometrically for the reaction to proceed. A model presented in this work uses the Gibbs free energy to predict the favorability of these byproducts as a function of temperature and pressure. At 0.1 MPa, this model predicts the primary favorability of Al(OH)3 (gibbsite) below 294 K, AlOOH (boehmite) from 294 to 578 K, and Al2O3 (corundum) above 578 K. The results of this model were tested using a previously established technique for activating bulk aluminum via infusion of a gallium-indium eutectic into its grain boundary network. Reaction tests were performed at the extremities of the operating range of interest, and the composition of the byproducts from each test, determined via Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis, were all in alignment with the model. Furthermore, reaction tests above 423 K at 0.1 MPa indicate limited reactivity of steam with aluminum activated in this manner. Consequently, the model is modified accordingly to show that Al2O3 cannot be achieved in practice with this method as its transition remains above the saturation temperature of water at the pressures studied here. [Display omitted] •Aluminum and water react to produce H2 and AlOOH (boehmite) at 1 bar above 294 K.•Al(OH)3 (gibbsite) is produced for temperatures below 294 K at 1 bar, or at high pressure.•A validated model shows under which conditions each byproduct is produced.•Above the saturation temperature of water, production of Al2O3 (corundum) is favored.